Literasi Digital Mengunakan Google Classroom Sebagai Media Pembelajaran di SMP Al Khaeriyah Pengampelan - Mursyid Irfan; Halimatus Sadiyah; Shella Ramanda Putri; Uus Khusnia; Nyssa Salwa (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to describe the implementation of Google Classroom as a digital literacy learning media at Al-Khaeriyah Pengampelan Junior High School. This research used descriptive qualitative method. Data were collected through observation, interviews and documentation. The results showed that Google Classroom was effective enough to be used as a digital literacy learning media at Al-Khaeriyah Pengampelan Junior High School. This is evidenced by the increase in students' knowledge and skills in using digital technology to find information, communicate, and collaborate.